2007
DOI: 10.1002/jnr.21483
|View full text |Cite
|
Sign up to set email alerts
|

Peptide hormone exendin‐4 stimulates subventricular zone neurogenesis in the adult rodent brain and induces recovery in an animal model of parkinson's disease

Abstract: We investigated the effects of exendin-4 on neural stem/progenitor cells in the subventricular zone of the adult rodent brain and its functional effects in an animal model of Parkinson's disease. Our results showed expression of GLP-1 receptor mRNA or protein in the subventricular zone and cultured neural stem/progenitor cells isolated from this region. In vitro, exendin-4 increased the number of neural stem/progenitor cells, and the number of cells expressing the neuronal markers microtubule-associated protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
231
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(244 citation statements)
references
References 60 publications
6
231
1
2
Order By: Relevance
“…Our findings indicate that the neuroprotective actions of GLP-1R agonists appear to effectively translate across a number of classic cellular and animal models, including stroke and PD, as well as cholinergic ablation (14), kainic acid-induced CA3 hippocampal loss (38), and peripheral neuropathy (35). In contrast, the Glp1r Ϫ/Ϫ mice demonstrated impaired learning, as well as increased brain injury and associated behaviors after a lesion (32).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our findings indicate that the neuroprotective actions of GLP-1R agonists appear to effectively translate across a number of classic cellular and animal models, including stroke and PD, as well as cholinergic ablation (14), kainic acid-induced CA3 hippocampal loss (38), and peripheral neuropathy (35). In contrast, the Glp1r Ϫ/Ϫ mice demonstrated impaired learning, as well as increased brain injury and associated behaviors after a lesion (32).…”
Section: Discussionmentioning
confidence: 82%
“…Together, the findings of these studies suggest a loss of function in -/-mice and a physiological role for GLP-1R activation in the normal brain, as in the pancreas, that can be augmented by pharmacologic concentrations of agonists and inhibited by antagonists. Recent studies have demonstrated that Ex-4 can induce neurogenesis of neural stem cells both in culture and in the subventricular zone of rat brain after a 6-OHDA insult (38,39) and promote differentiation toward a neuronal phenotype (38), as has been reported for PC12 cells (13). Ex-4's ability to improve dopaminergic markers and function when administered a week or more after 6-OHDA-or cytokine-induced apoptosis, rather than at the time of insult as in our study, is indicative of neuroregenerative action (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…3 In addition, GLP-1R activation promotes synaptic plasticity and neurite outgrow 3 and can stimulate adult neurogenesis (Figure 1). 30 The findings could form the bases for potential regenerative therapy for chronic stroke patients. At this regard, experimental data and future work are highly needed.…”
Section: Potential Mechanisms and Future Directionsmentioning
confidence: 97%
“…Several recent discoveries have highlighted common cellular pathways that potentially relate neurodegenerative processes with abnormal mitochondrial function and abnormal glucose metabolism [2]. In parallel with these advances, a treatment for insulin resistance (exenatide; a GLP-1 agonist) has been proposed as a disease modifying drug in PD, based on multiple in vitro and in vivo studies [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%